How Does Value Creation Manifest Itself in the Nexus of Sport and Business?: A Systematic Literature Review - Harri Jalonen; Sasu Tuominen; Arto Ryömä; Jaakko Haltia; Juho Nenonen; Anna Kuikka (Scientific Research Publishing, Inc., 2022)
Sport is a widely used as a vehicle for promoting business. Global brands invest tens of millions of euros in high performance athletes, top teams, and popular sporting events. Studies have also shown the potentiality of sport in the business context. However, relatively few studies have focused on the interaction of business and sport from a value-creation perspective. Knowledge focusing on value creation within and through sport is scattered throughout literature and a systematic understanding of how value creation manifests itself in a business context is lacking. Using a systematic literature review and inductive analysis of 44 empirical studies, the article presents six identified topics that represent the various angles to value creation in the nexus between sport and business. The topics are 1) the many shades of value, 2) brands and sponsorship as value-creators, 3) the value of CSR in and through sport, 4) sport as a network and platform, 5) sport for developing organisations internally, and 6) value congruence and identification. The article contributes to both business management and sports management. The article proposes theoretical and managerial implications and identifies avenues for further research.